Inspeksi keselamatan jalan di Ruas Jalan Hang Tuah-Mayjend D.I. Panjaitan Kota Tegal - Suprapto Hadi; Asyhari Wijaya; Dzakiyya Salsabila Afifi; M. Daffa Izzuddin; Rahmat Rizki Ananda (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2026)
Roads play an important role in supporting community mobility, goods distribution, and regional economic growth. However, poor road conditions, inadequate geometric design, and incomplete traffic facilities often increase the risk of traffic accidents. The Hang Tuah–Mayjend D.I. Panjaitan Road corridor in Tegal City serves as a major urban route with dense traffic and mixed vehicle movements. This study aims to conduct a comprehensive road safety inspection by integrating the Hazard Identification, Risk Assessment and Risk Control (HIRARC) method with the Surface Distress Index (SDI) approach. The HIRARC method was used to identify hazards, assess risk levels, and determine appropriate risk control measures, while the SDI method was applied to evaluate pavement conditions based on surface distress observations. The results indicate that the main hazards found along the corridor include roadside activities, geometric deficiencies, inadequate traffic signs, and construction materials located on the roadside. The HIRARC analysis showed that most identified hazards were classified as medium risk with risk values ranging from 6–12, while the highest risk was caused by roadside construction materials with a risk value of 15. Meanwhile, the SDI assessment revealed that all road segments were categorized as being in good condition with SDI values ranging from 15–30, indicating that the pavement damage was still local in nature and only required routine maintenance. The integration of HIRARC and SDI demonstrates that good pavement conditions do not necessarily guarantee low safety risks, as operational factors and roadside obstacles remain dominant contributors to potential traffic accidents along the road corridor.